M advertising - Arens, William; Schaefer, David H.; Weigold, Michael F. (McGraw-Hill Education, 2015)
Chapter 1: The evolution of advertising -- Chapter 2: The environment of advertising -- Chapter 3: The business of advertising -- Chapter 4: Segmentation, targeting, and the marketing mix -- Chapter 5: Communication and consumer behavior -- Chapter 6: Account planning and research -- Chapter 7: Marketing, advertising, and IMC planning -- Chapter 8: Creating ads (strategy and process) -- Chapter 9: Creative execution (art and copy) -- Chapter 10: Print advertising -- Chapter 11: Broadcast, cable, and satellite media (television and radio) -- Chapter 12: Digital interactive media -- Chapter 13: Out-of-home, direct-mail, and promotional products -- Chapter 14: Media planning and buying -- Chapter 15: IMC (direct marketing, personal selling, packaging, and sales promotion -- Chapter 16: IMC (public relations, sponsorship, and corporate advertising